Essays on the fiscal aspects of trade liberalisation - Samuels, Dacia Astaire (2017)
This thesis comprises a series of three studies that explore the impact of trade reform on fiscal revenue. Two of the studies use cross-country econometric methods and the third utilizes a partial equilibrium approach to analyse the impact of trade liberalisation on tax revenue and welfare in Jamaica. The first study examines the impact of trade liberalisation on total revenue and trade tax revenue as a share of GDP across countries, explores heterogeneity within the sample (in particular the extent to which a country’s level of development influences variations in the effects of trade liberalisation) and utilises alternative indicators of openness to determine if the findings of the model are sensitive to the indicator of openness used. The study finds that, in the case of the openness index used by Khattry and Rao (2002), international trade tax and total tax revenue as a percent of GDP are likely to rise as an economy becomes less open. In contrast, when trade as a percent of GDP is used as the indicator of openness, the results show a positive relationship between openness, and trade and total tax revenue as a share of GDP. The results also suggest that international trade tax revenue tends to fall over time as a country develops. The second study uses events analysis to examine the same issue. There is weak evidence that trade reform has positive revenue effects in the long-run; however, there may be negative impacts within a year of reform. The third study explores the impact of trade liberalisation under the EU-CARIFORUM Economic Partnership Agreement (EPA) on Jamaica by simulating different tariff reform scenarios and comparing the results with the end term EPA as negotiated. It finds that small countries can devise appropriate strategies to mitigate potential negative fiscal effects of trade reform such as scheduling tariff reductions for high revenue items later in the reform process. It also finds that there is often a trade-off between revenue and welfare, which makes welfare increasing and revenue enhancing outcomes difficult to achieve.